2021
DOI: 10.1111/echo.14970
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava dilation predicts global cardiac dysfunction in acute respiratory distress syndrome: A strain echocardiographic study

Abstract: Purpose Limited data exist on the utility of ultrasonographic evaluation of inferior vena cava (IVC) in acute respiratory distress syndrome (ARDS). We studied the value of IVC diameter in assessing cardio‐circulatory performance in ARDS using strain echocardiography. Materials and Methods Retrospective cross‐sectional analysis of Doppler echocardiograms of patients with moderate–severe ARDS was performed. Right ventricle (RV) parameters, IVC diameter, and left ventricle (LV) systolic and diastolic parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…The morphology of IVC is frequently used to estimate right atrial pressure; however,the relationship between IVC morphology and RV outcomes has not been clarified completely 18 . Dilated IVC cases were found to be associated with RV dysfunction, high central venous pressure, and high pulmonary artery pressure 19 . High PVR can lead to IVC dilatation along with PH and RV deficiency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The morphology of IVC is frequently used to estimate right atrial pressure; however,the relationship between IVC morphology and RV outcomes has not been clarified completely 18 . Dilated IVC cases were found to be associated with RV dysfunction, high central venous pressure, and high pulmonary artery pressure 19 . High PVR can lead to IVC dilatation along with PH and RV deficiency.…”
Section: Discussionmentioning
confidence: 98%
“…High PVR can lead to IVC dilatation along with PH and RV deficiency. Some studies showed that IVC dilatation was one of the early indicators of disrupted hemodynamics in shock patients 19 . The mechanism of RV dilatation is multifactorial, and it involves thrombotic events, hypoxemic vasoconstriction, cytokines and direct viral damage.…”
Section: Discussionmentioning
confidence: 99%
“…IVC dilatation had been suggested as a potential predictor of outcome in many different clinical contexts [ 64 , 65 , 66 ]. However, numerous physiological and pathophysiological conditions, as well as several interpretive pitfalls, have limited its wide applicability [ 24 ].…”
Section: Pitfalls That May Lead To Misinterpretation Of Volume Statusmentioning
confidence: 99%